Artificial Inclusion Environments—Replicating Industry in the Laboratory - Raviraj, A.; Spooner, S.; Li, J.; Kourra, N.; Warnett, J.; Abbel, G.; Tiekink, W.; Williams, M. A.; Davis, C.; Sridhar, S. (Frontiers in Materials, 2021)
The authors present a series of complementary test methods which were developed and used to investigate reactions between high aluminum steel and silica rich inclusions. Non-metallic inclusions (NMIs) cause many defects in the final steel product, therefore the ability to track their size, morphology and composition and correlate this with fundamental reaction kinetics provides important knowledge to support the production of clean quality steel products. Novel steel grades such as TRIP, TWIP and low-density steels have high aluminum contents; aluminum is a readily oxidisable species presenting the potential for instability and excessive reaction with commonly used mould powders that contain silica. A novel combination of techniques including HT-CLSM (High-Temperature Confocal Laser Scanning Microscope), XCT (X-ray computed tomography) and SEM/EDS (scanning electron microscopy/electron dispersive spectroscopy) have been used to study the interaction of entrained mould powder inclusions with steel at high temperatures simulating industrial conditions. This report presents a discussion on the development of techniques and samples to achieve representative and repeatable results that can provide information on the complex chemical and physical interaction phenomena with confidence. Each experimental technique had its own learning points and consequent results. Outcomes presented include confirmation of the chemical reaction rate controlling step being aluminum mass transfer; heterogeneous local environmental conditions including fluidity and chemical composition; and occurrence of spontaneous emulsification where the mould powder inclusion breaks apart into a cloud of smaller fragments.